2017
DOI: 10.31234/osf.io/cujqf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Encoding context determines risky choice

Abstract: Both memory and choice are influenced by context: Memory is enhanced when encoding and retrieval contexts match, and choice is swayed by available options. Here, we assessed how context influences risky choice in an experience-based task. Within a single session, we created two separate contexts by presenting blocks of trials in distinct backgrounds. Risky choices were context-dependent; given the same choice, people chose differently depending on other outcomes experienced in that context. Choices reflected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Their decision-making task had a limited set of decision outcomes and did not directly test memory accuracy, making it more di cult to determine the extent to which participants were relying on recall of speci c instances. Interestingly, the risk preferences (and memory recall patterns) in the current study are consistent with prior ndings that use a smaller set of outcomes (Konstantinidis, Taylor, & Newell, 2018;Madan et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Their decision-making task had a limited set of decision outcomes and did not directly test memory accuracy, making it more di cult to determine the extent to which participants were relying on recall of speci c instances. Interestingly, the risk preferences (and memory recall patterns) in the current study are consistent with prior ndings that use a smaller set of outcomes (Konstantinidis, Taylor, & Newell, 2018;Madan et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…This description-experience gap has been attributed to a process of drawing samples from memory (Hertwig & Erev, 2009), which might only feature a small subset of past experiences (Plonsky, Teodorescu, & Erev, 2015) or can be explicitly biased (Madan et al, 2017). In our previous work, using a risky-choice paradigm, we have consistently found that people overweight the extreme outcomes (highest and lowest in a context) in memory (Madan et al, 2014;Madan, Spetch, Machado, Mason, & Ludvig, 2021). This overweighting in memory leads to people being more risk-seeking for choices that involve the high extreme and less risk-seeking for choices that involve the low extreme.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thirdly, the relative payout effect suggests that the best and worst payouts of a gambling experience may disproportionately affect behavior. In studies using doors as choice stimuli, we found that relative payout effects were specific to a particular episode and set of cues . Therefore, in a casino, overweighting of the best and worst payout is probably based on a specific gambling episode rather than the entire set of gambling experiences.…”
Section: Discussionmentioning
confidence: 85%
“…The extreme-outcome rule only manifests when outcomes are learned through experience rather than being described, and it requires the intermixing of choices involving relative gains and losses within the same context. For example, the absolute level of risk preference for a choice between a fixed option leading to +20 points and a risky option leading to either +10 or +30 points, depends on whether the choice occurs in the context of other choices that involve losses or other choices that involve higher valued gains (see Madan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%